ASFV infection induces macrophage necroptosis and releases proinflammatory cytokine by ZBP1-RIPK3-MLKL necrosome activation - Zhang, Dajun; Hao, Yu; Yang, Xing; Shi, Xijuan; Zhao, Dengshuai; Chen, Lingling; Liu, Huanan; Zhu, Zixiang; Zheng, Haixue (Frontiers in Microbiology, 2024)
African swine fever (ASF) is an infectious disease characterized by hemorrhagic fever, which is highly pathogenic and causes severe mortality in domestic pigs. It is caused by the African swine fever virus (ASFV). ASFV is a large DNA virus and primarily infects porcine monocyte macrophages. The interaction between ASFV and host macrophages is the major reason for gross pathological lesions caused by ASFV. Necroptosis is an inflammatory programmed cell death and plays an important immune role during virus infection. However, whether and how ASFV induces macrophage necroptosis and the effect of necroptosis signaling on host immunity and ASFV infection remains unknown. This study uncovered that ASFV infection activates the necroptosis signaling in vivo and macrophage necroptosis in vitro. Further evidence showed that ASFV infection upregulates the expression of ZBP1 and RIPK3 to consist of the ZBP1-RIPK3-MLKL necrosome and further activates macrophage necroptosis. Subsequently, multiple Z-DNA sequences were predicted to be present in the ASFV genome. The Z-DNA signals were further confirmed to be present and colocalized with ZBP1 in the cytoplasm and nucleus of ASFV-infected cells. Moreover, ZBP1-mediated macrophage necroptosis provoked the extracellular release of proinflammatory cytokines, including TNF-α and IL-1β induced by ASFV infection. Finally, we demonstrated that ZBP1-mediated necroptosis signaling inhibits ASFV replication in host macrophages. Our findings uncovered a novel mechanism by which ASFV induces macrophage necroptosis by facilitating Z-DNA accumulation and ZBP1 necrosome assembly, providing significant insights into the pathogenesis of ASFV infection.